1973
DOI: 10.1126/science.180.4083.261
|View full text |Cite
|
Sign up to set email alerts
|

Megagauss Physics

Abstract: Fields greater than 10 MG can be produced by explosive flux compression and fields up to 3 MG with capacitor banks. Measurement of fields up to 10 MG is reliable, but difficulties may be expected at higher fields. Megagauss fields have been applied successfully as high-pressure sources, in high-energy particle physics, and in solid-state investigations. Other uses remain to be exploited: plasma compression by megagauss fields has been relatively unsuccessful but shows promise; their use as particle accelerator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In agreement with previous results [12,13] it was found that the rotation angle was almost linear as a function of the magnetic field, as demonstrated in figure 5. Nonlinearities of the effect have been reported in the literature [14], but these phenomena occur in a field range far beyond our experimental possibilities and preferably at shorter wavelengths [15]. The theoretical field dependence of the rotation angle deduced from the generally accepted value of the Verdet constant, V = 7.2 • (mm −1 T −1 ), coincides very well with our experimental results, thus confirming the high precision of our field measurements.…”
Section: The Faraday Rotationsupporting
confidence: 91%
“…In agreement with previous results [12,13] it was found that the rotation angle was almost linear as a function of the magnetic field, as demonstrated in figure 5. Nonlinearities of the effect have been reported in the literature [14], but these phenomena occur in a field range far beyond our experimental possibilities and preferably at shorter wavelengths [15]. The theoretical field dependence of the rotation angle deduced from the generally accepted value of the Verdet constant, V = 7.2 • (mm −1 T −1 ), coincides very well with our experimental results, thus confirming the high precision of our field measurements.…”
Section: The Faraday Rotationsupporting
confidence: 91%
“…Ultrahigh magnetic fields have been generated by imploding a conducting shell (liner) around a magnetic flux, for example, using high explosives [11] or high current [12].…”
mentioning
confidence: 99%
“…The very first experiments, on the Faraday and Zeeman effects, were mainly demonstrations that experiments could actually be done, and precise verifications of the field measurement [96]. Further experiments at Los Alamos were mainly done with 'strip' compression generators, both optical and magneto-resistance experiments at temperatures down to the liquid helium range [45,47,49,55]. At Livermore, the isentropic compression of hydrogen was extensively studied with fields of order 10 MG [63].…”
Section: Merits For Experimental Applicationsmentioning
confidence: 99%